Surface texture of laser-fabricated helical microgrooves on pressure swirl nozzles for enhanced atomization characteristics - Shenghan Cao; Jianxin Deng; Shiyao Rong; Yichen Bao; Junyan Wang; Zhihui Zhang (Crop Protection, 2026)

Coupled acid–salt erosion mechanism of solid waste–based grouting materials for submarine tunnels - Jun Ma; Weiyu Liu; Annan Jiang; Yichen Deng; Jiale Zhao; Tianmiao Qu; Chao He (Marine Georesources & Geotechnology, 2026)

High-titer de novo raspberry ketone production in Yarrowia lipolytica via precursor supply engineering and fed-batch fermentation optimization - Yuanyuan Li; Shuhao Niu; Zixuan Wang; Yichen Wang; Xiaojuan Zhang; Yu Deng; Shenghu Zhou (Bioresource Technology, 2026)

Comparative transcriptomic and metabolomic analyses reveal different tolerance mechanisms to heat stress in two geographic populations of Argopecten irradians concentricus - Min Shen; Shaoxuan Wu; Oscar Yichen Liu; Jinjing Wang; Guilong Liu; Xin Xu; Zhigang Liu; Yuewen Deng; Junhao Ning; Chunde Wang (Aquaculture, 2026)

Resilience assessment of interdependent transit networks: an indifference perception threshold-based approach - Yichen Liang; Yajuan Deng; Chen Zhang; Ketong Hao; Yujie Guo; Yu Li; Liangbin Cui (Transportation Research Part D: Transport and Environment, 2026)

Comparative metabolomics of Lycium barbarum seeds from different regions: variations in bioactive compounds and antioxidant potential - Rongyi Gong; Yichen Liu; Xinyan Wu; Qian Wang; Wenyuan Zhang; Jianjun Deng; Xiaojie Yang; Yaqi Zhao; Haixia Yang (Food Chemistry, 2026)

Vapor pretreatment-mediated crystal quality optimization for all-vacuum-processed monolithic perovskite/silicon tandem solar cells - Yichen Dou; Changyu Duan; Shenghan Hu; Xinyu Deng; Yuanyuan Chen; Anqi Kong; Yong Peng; Xiong Li; Zhiliang Ku (Chemical Engineering Journal, 2026)

Integrative Assessment of Interrelated Swimming Performances and their Physiological Basis in Large Yellow Croaker (Larimichthys crocea) - Wei Liu; Junjia Zeng; Jiaxing Liu; Tingsen Jiang; Yacheng Deng; Pengxin Jiang; Yin Li; Ningyuan Ding; Yichen Li; Yujia Chen; Chuan Deng; Haojie Li; et al. (Marine Biotechnology, 2026)

On field measurement for absorption properties of biomass burning aerosols in the North China Plain and climate implications - Yang Wang; Yansong Xu; Ruonan Bian; Junjun Deng; Yichen Ma; Song Guo; Jing Wang (Science China Earth Sciences, 2026)

Analysis on the difference of nutrient components of black wolfberry seed grown in different regions - Yichen Liu; Wenyuan Zhang; Yanjun Li; Ruhui Shen; Shuaibei Wang; Xue Wang; Jianjun Deng; Zhenzhen Xu; Haixia Yang (Food Research International, 2025)

Two-dimensional surface induced strategy enabling high-quality halide perovskite thin film growth via vapor-solid reactions - Meichen Liu; Shenghan Hu; Changyu Duan; Xinyu Deng; Yichen Dou; Mengjun Liu; Yuanbo Song; Tiancan Zhang; Guijie Liang; Zhiliang Ku (Chemical Engineering Journal, 2025)

Microwave-assisted one-pot synthesis of hierarchical MnCO3/NiO heterojunction with superior energy storage performance for aqueous supercapacitor - Yin Sun; Gaoyong Zhang; Shuhuang Tan; Haowei Wang; Yichen Liu; Chengqi Sun; Banglin Deng; Kun Zhang; Zhaoqing Gao; Naibao Huang (Chemical Engineering Journal, 2025)

Editorial: One climate, one urban, one health - Guangtao Fan; Yichen Yu; Meng Gao; Ayyoob Sharifi; Minal Pathak; Kai Zhang; Pablo Fernández de Arróyabe Hernáez; Qihong Deng (Sustainable Cities and Society, 2025)

Human dental follicle cell-derived conditioned media enhance periodontal regeneration by regulating the osteogenic differentiation and inflammation of periodontal ligament stem cells and macrophage polarization - Yichen Gao; Xianyi He; Yuyao Deng; Xia Wang; Jie Shen; Wei Xu; Rui Cai; Xiaorong Lan; Junliang Chen; Yun He (Molecular and Cellular Biochemistry, 2025)

Magmatic dikes in the Chang'e-6 sampling area - Qingyun Deng; Zhiyong Xiao; Yunhua Wu; Pei Ma; Wei Cao; Yichen Wang; Yizhen Ma; Fanglu Luo; Fei Li (Earth and Planetary Science Letters, 2025)

Dynamic changes in flavor characteristics of black tea during solid-state fermentation with Eurotium cristatum - Linyao Song; Fengwei Ma; Haijiang Chen; Qiang Fei; Guangcan Tao; Siyao Wu; Dajuan Shi; Junyi Deng; Degang Zhao; Xuan Dong; Yichen Zhao; Su Xu (Food Chemistry, 2025)

Comparison analysis of bioactive metabolites in soybean, pea, mung bean, and common beans: reveal the potential variations of their antioxidant property - Wenyuan Zhang; Yaqi Zhao; Haixia Yang; Yichen Liu; Yanli Zhang; Zhanquan Zhang; Yunlong Li; Xue Wang; Zhenzhen Xu; Jianjun Deng (Food Chemistry, 2024)

Unveiling the role of Cs ion in perovskite phase formation during solid–vapor reactions - Shenghan Hu; Peiran Hou; Changyu Duan; Shuang Zeng; Yichen Dou; Xinyu Deng; Yuxi Zhang; Jianfeng Lu; Yi-Bing Cheng; Yong Peng; Zhiliang Ku (Chemical Engineering Journal, 2024)

Impact of biochar synergized bacteria on Mn2+ and NH4+-N removal and CO2 immobilization in water by enhanced extracellular electron transfer - Shuman Deng; Qiang An; Weifeng Zhang; Zheng Li; Jiali Song; Yichen Yang; Bohan Xu; Binbin Ran; Bin Zhao (Journal of Environmental Chemical Engineering, 2024)

Enhancement of Mn2+, Fe2+ and NH4+-N removal by biochar synergistic strains combined with activated sludge in real wastewater treatment - Shuman Deng; Qiang An; Jiali Song; Yichen Yang; Zhiruo Huang; Shuyun Feng; Chuanzhu Tang; Bin Zhao (Chemosphere, 2024)

Comparisons of procyanidins with different low polymerization degrees on prevention of lipid metabolism in high-fat diet/streptozotocin-induced diabetic mice - Tong Zhao; Dan Liu; Yichen Liu; Jianjun Deng; Haixia Yang (Food Research International, 2024)

Time-Lapse Macro Imaging with Dissolution Tests for Exploring the Interrelationship Between Disintegration and Dissolution Behaviors of Solid Dosages - Yichen Yang; Jiajia Gengji; Tao Gong; Zhirong Zhang; Li Deng (Pharmaceutical Research, 2024)

Disrupted morphological brain network organization in subjective cognitive decline and mild cognitive impairment - Yuxin Chen; Lingyan Liang; Yichen Wei; Ying Liu; Xiaocheng Li; Zhiguo Zhang; Linling Li; Demao Deng (Brain Imaging and Behavior, 2023)

Altered regional homogeneity following moxibustion in mild cognitive impairment - Qingping Zhang; Lingyan Liang; Ziyan Lai; Yichen Wei; Gaoxiong Duan; Yinqi Lai; Peng Liu; Demao Deng (Brain Imaging and Behavior, 2023)

Removal of iron, manganese and ammonium from contaminated mine water by biochar immobilized Acinetobacter sp. AL-6 under acid condition, and the role of extracellular polymeric substances - Shuman Deng; Qiang An; Jiali Song; Yichen Yang; Zhiruo Huang; Bin Zhao (Journal of Cleaner Production, 2023)

Fractional grey unequal-interval time-varying Lotka-Volterra model and its application for microbial communities in compost - Yichen Liu; Bing Deng; Peng Gu; Zhenyu Pu; Xinping Xiao; Congjun Rao; Jianghui Wen (Waste Management, 2023)

Dynamic response analysis of a floating vertical axis wind turbine with helical blades based on the model test - Wanru Deng; Ying Guo; Liqin Liu; Yan Li; Yichen Jiang; Peng Xie (Ocean Engineering, 2023)

Spatiotemporal variations in meteorological influences on ambient ozone in China: A machine learning approach - Tao Li; Yichen Lu; Xunfei Deng; Yu Zhan (Atmospheric Pollution Research, 2023)

Lonp1 and Sig-1R contribute to the counteraction of ursolic acid against ochratoxin A-induced mitochondrial apoptosis - Qipeng Zhang; Wenying Chen; Boyang Zhang; Yiwen Zhang; Yuqing Xiao; Yichen An; Lingyun Han; Huiqiong Deng; Song Yao; Hongwei Wang; Xiao Li Shen (Food and Chemical Toxicology, 2023)

Continuous flow modulates zein nanoprecipitation solvent environment to obtain colloidal particles with high curcumin loading - Haocheng Guo; Yiming Feng; Yong Deng; Tianyi Yan; Zimo Liang; Yichen Zhou; Wei Zhang; Enbo Xu; Donghong Liu; Wenjun Wang (Food Hydrocolloids, 2023)

Characteristics of Slamming Pressure and Force for Trimaran Hull - Zhe Sun; Xupeng Sui; Yanzeng Deng; Li Zou; A. Korobkin; Lixin Xu; Yichen Jiang (Journal of Marine Science and Engineering, 2021)
In this paper, the characteristics of the impact pressure and force of a trimaran section was studied by Computational Fluid Dynamics (CFD). The time domain features of the slamming pressure or force showed a strong correlation with the penetration depth regardless of the specific ways of water entry. The effects of velocity and acceleration on the impact pressure and force were analyzed. It was found that the initial impact of the main hull and the wet-deck slamming were predominantly affected by the entry velocities, whilst the acceleration had almost no effect for initial impact. The impact velocity presented a quadratic relation with slamming pressure/forces, and the relation between acceleration and wet-deck slamming pressure/force was linear. These were consistent with the patterns implied by analytical models such as the Wagner or MLM (Modified Logvinovich model) theories.

Levo-tetrahydropalmatine Attenuates Neuron Apoptosis Induced by Cerebral Ischemia–Reperfusion Injury: Involvement of c-Abl Activation - Ruoxi Sun; Yichen Song; Shanshan Li; Zhanqiang Ma; Xueyang Deng; Qiang Fu; Rong Qu; Shiping Ma (Journal of Molecular Neuroscience, 2018)